Divergent gene expression of PTGS1 and PTGS2 along the disease course of chronic myeloid leukaemia - Wosniaki, Denise K.; Kusma, Bianca N.; Marin, Anelis M.; Munhoz, Eduardo C.; Farias, João S. de H.; Mendes, Eduarda B.; Aoki, Mateus N.; Zanette, Dalila L. (Frontiers in Oncology, 2025)
IntroductionChronic myeloid leukaemia (CML) is a chronic myeloproliferative disorder caused by the reciprocal translocation of chromosomes 9 and 22. This genetic abnormality leads to the uncontrolled proliferation of myeloid lineage cells, ultimately causing leukaemia. Inflammation plays a significant role in the progression of various cancers, including lungs, colorectal, breast, head and neck, and haematological malignancies. Prostaglandins, which are key mediators in these processes, are synthesised by cyclooxygenases. Consequently, these genes are critical targets for studying CML due to their involvement in leukemogenesis.MethodsWe investigated the expression levels of PTGS1 and PTGS2 genes in peripheral blood samples from CML patients. Quantitative PCR (qPCR) and in vitro cell culture experiments were used to assess gene expression. Statistical analysis included the Kruskal–Wallis test and simple linear regression models. Patients were stratified according to disease status, BCR::ABL1 levels, treatment-free remission (TFR), and use of imatinib. The impact of NSAID use on gene expression was also evaluated.ResultsIncreased expression of PTGS1 and PTGS2 was observed in patients with favourable prognosis. Conversely, lower expression levels were found in patients with uncontrolled disease (high BCR::ABL1 levels) compared to healthy controls, those in TFR, and patients undergoing imatinib treatment. NSAID use did not significantly alter PTGS gene expression. In vitro treatment of a CML cell line with imatinib also showed increased PTGS1 expression.DiscussionThese findings suggest a potential role of inflammatory pathways in CML progression and treatment response. The upregulation of PTGS1 and PTGS2 in patients with controlled disease and after imatinib treatment may indicate a link between COX enzyme activity and leukemogenesis. Further investigation is warranted to clarify the mechanistic role of these genes in CML pathophysiology and therapy outcomes.